Coral reefs of the Indian Ocean : their ecology and conservation - McClanahan, T. R.; Sheppard, Charles (Charles R. C.); Obura, David O. (Oxford University Press, 2000)
Accessible and complex, coral reefs are ideal natural laboratories for studying a wide range of ecological and biological questions. This collection focuses on the Indian Ocean and the Red Sea, which contain some of the most spectacular reefs found anywhere and which are relatively little studied.